Reassessment of the hairy long-nosed armadillo “Dasypus” pilosus (Xenarthra, Dasypodidae) and revalidation of the genus Cryptophractus Fitzinger, 1856 - Castro, Mariela C. (2015)
The hairy long-nosed armadillo, currently referred as Dasypus (Cryptophractus) pilosus, is an enigmatic species endemic to montane cloud forests and subparamo of Peruvian Andes. Its strikingly different external features, which include the carapace concealed by abundant hair, the presence of more movable bands, and a slender skull, have raised questions regarding its taxonomic status as subgenus or as genus. This paper assesses this issue based on a cladistic study and provides a detailed comparative description of the species, including the first account on the distinctive ornamentation of its osteoderms. Based on several unique characters in the carapace, skull, mandible, and teeth, as well as on the external phylogenetic position relative to other Dasypus, we favor the assignment of the hairy long-nosed armadillo to other genus. As result, we revalidate the original generic epithet, so that the valid name of the species is Cryptophractus pilosus Fitzinger, 1856.